1982
DOI: 10.1037/0278-7393.8.6.619
|View full text |Cite
|
Sign up to set email alerts
|

Signs as pictures and signs as words: Effect of language knowledge on memory for new vocabulary.

Abstract: The role of sensory attributes in a vocabulary learning task was investigated for a non-oral language. Deaf and hearing individuals, more or less skilled in the use of sign language, were asked to learn the English meanings of 22 invented signs which followed the rules of formation for signs in American Sign Language. Each sign stimulus was highly similar in formation to another sign in the set. It was expected that skilled signers would be less affected by this formational similarity because of their greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Poizner interpreted the effect as being the visual analogue of the differential auditory perception that speakers show for phonemes from a "native" as opposed to a "foreign" language. In a learning study, Siple, Caccamise, and Brewer (1982) found the skill level of deaf and normally hearing signers (specifically, "skilled, intermediate, and unskilled") to predict the speed with which they could learn associations between written English words and nonsense signs. More importantly, the rank order of stimulus difficulty for the skilled signers was predicted by a set of distinctive features proposed for ASL handshapes (Lane, Boyes-Braem, & Bellugi, 1976), whereas the performance of the unskilled signers was not.…”
Section: Sign Language Processingmentioning
confidence: 99%
“…Poizner interpreted the effect as being the visual analogue of the differential auditory perception that speakers show for phonemes from a "native" as opposed to a "foreign" language. In a learning study, Siple, Caccamise, and Brewer (1982) found the skill level of deaf and normally hearing signers (specifically, "skilled, intermediate, and unskilled") to predict the speed with which they could learn associations between written English words and nonsense signs. More importantly, the rank order of stimulus difficulty for the skilled signers was predicted by a set of distinctive features proposed for ASL handshapes (Lane, Boyes-Braem, & Bellugi, 1976), whereas the performance of the unskilled signers was not.…”
Section: Sign Language Processingmentioning
confidence: 99%
“…They also sketched how many signs appear to lose some of their iconicity as they mature, for example because their form is slightly changed to conform to the phonological categories of a language or because the action they denote is no longer a part of normal, everyday culture. Some findings even seem to show that iconicity does not play an important or active role in the perception of iconic signs (Siple et al 1982;Newport & Meier 1985) or in their production (Marshall et al 2004;Emmorey et al 2004) at all. However, the current findings are an indication that, at least when signers have to make acceptability judgments of highly variable sign manipulations, iconicity does play a role.…”
Section: Iconicity: Only When Necessary?mentioning
confidence: 88%
“…If one regards iconicity as a fairly complex strategy to interpret the meaning of signs, it might then be reasonable to expect that iconicity only plays a role if a straightforward symbolic interpretation is not possible or does not suffice, for example, if one has to judge the acceptability of a sign manipulation or if one sees an unknown sign or gesture. Perhaps in the studies by Siple et al (1982), Newport & Meier (1985), Marshall et al (2004), and Emmorey et al (2004) people did not have to rely on iconicity even though they were dealing with iconic signs. There are several indications that seeing iconicity is indeed a fairly complex matter and not something that necessarily occurs whenever you look at an iconic sign.…”
Section: Iconicity: Only When Necessary?mentioning
confidence: 95%
“…However, there is evidence that hearing non-signers do not immediately process signs linguistically, instead processing them as nonverbal movements (Martinez & Singleton, 2018;Newman-Norlund, Frey, Petitto, & Grafton, 2006;Siple, Caccamise, & Brewer, 1982; J. T. Williams, Darcy, & Newman, 2016b). The other two common processing components, perceptual and motor processes, are undoubtedly different across signed and spoken languages.…”
Section: Phonological Short-term Memory In Signed and Spoken Languagesmentioning
confidence: 99%
“…For example, the ability to disengage from outdated material may be related to the ability to mitigate proactive interference (Engle, 2018;Shipstead et al, 2016)although attempts were made to reduce item similarity, the sign stimuli may not have been distinct enough compared to the spoken language material. Indeed, there is evidence that sign similarity has a greater detrimental effect on learning of novel signs in hearing non-signers compared to proficient signers (Siple et al, 1982). Clearly, more research is needed to investigate whether the magnitude of the correlations exhibited between the PSTM factors and fluid intelligence generalize and, if so, the cause.…”
Section: The Specificity and Generality Of Phonological Short-term Mementioning
confidence: 99%